‘A Space Together and Apart’ – A Qualitative Study of the Meaning of Therapeutic Space - Wayne, Susan (2013)
This qualitative study takes a phenomenological approach to explore understandings of the meaning of ‘therapeutic space’ in a wide sense, both conceptually and as experienced by counsellor and client. It includes a literature review, initial heuristic reflections and an interpretative phenomenological analysis of data from semi-structured interviews with three experienced counsellors and two centre managers. The study found that the meaning and experiencing of therapeutic space consolidated into four main themes and two more cross cutting themes. These are: